(untitled) (Journal of Laboratory Animal Science, 2022)
Wound dressing is an integral technique of animal care in various studies involving animal models. This post-operative technique often determines the mortality and morbidity of the animal used and also influences experimental outcomes. Post auricular surgical wounds presents a challenge for dressing on account of presence of sense organs in the vicinity. Rats are also prone to damaging the dressing and the underlying sutures. Hence, an appropriate technique for dressing the region is vital for successful surgical outcomes. Literature on dressing of post auricular surgical wounds in rats are scarce. The present work describes in detail the wound dressing technique in adult Wistar rats developed by the authors. A total of 14 animals were used for the study and with this technique, the wrap around the incision was found to be intact till the next day of post-operative dressing. The wound healing process appeared to be normal with no visible signs of infection at the incision.